The Influence of Employee Discipline Levels on the Performance of the Production Department at PT. Perkebunan Nusantara XIV Makassar - Wa Ode Sufiati; Muh. Nur; Asri Jaya (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is: To determine the effect of employee discipline on the performance of production employees at PT Perkebunan Nusantara XIV. The type of research carried out was quantitative with an associative approach. The population in this study were all employees in the production section at PT Perkebunan Nusantara XIV Makassar, totaling 114 people. The sampling technique used by the author is nonprobability sampling. Based on this, the sample in this study is the entire population taken, namely all production employees at PT Perkebunan Nusantara XIV Makassar, totaling 114 people. The results of this research are that employee discipline has a calculated t value of 11.595 which is greater than the t table of 1.981 (11.595 > 1.981) with a probability of a significant level of 0.000 which is smaller than the significant level of 0.05, so the hypothesis is accepted. This means that employee discipline has a positive and significant effect on the performance of production employees. The results of this research show that the better the employee discipline, the better the performance of production employees will be. Without good discipline, it will be difficult for a company to achieve optimal results so that the performance of production employees will not be optimal.